Effects of theaflavins rich fraction on pro-inflammatory markers and oxidative stress in stimulated endothelial cells / Remee Awang Jalil - Awang Jalil, Remee (2016)
Activation of endothelial cells (ECs) occurs early in atherogenesis leading to increased pro-inflammatory environment in the vessels. Oxidative stress also has been linked to atherogenesis, by promoting inflammatory environment and reduced nitric oxide availability in endothelium. Theaflavins rich fractions (TFs-RF) from black tea, Camellia sinensis are believed to promote cardio protective benefits. However, their potential therapeutic roles as anti-inflammatory and anti-oxidative in atherogenesis are not well established. The objectives of this study were to investigate (i) the anti-inflammatory effects of TF-RFs on cytokines [Interleukin-6 (IL-6), and tumour necrosis factor alpha (TNF-a)] , cyclooxygenase-2 (COX-2), endothelial nitric oxide synthase (eNOS) and nitric oxide (NO), and (ii) the anti-oxidative effects of TFs-RF on reactive oxygen species (ROS) activity in stimulated human ECs. Cytotoxicity of TFs-RF (1.6 - 200 |xg/ml) towards Human umbilical vein endothelial cells (HUVECs) were assessed by using 3-(4,5-dimethylthiazol-2-yl)-5(3-carboxymethoxyphenyl)- tetrazolium (MTS) assay. Confluent HUVECs were incubated with 10, 20, 30, 40 and 50 |ig/ml of TFs-RF together with lipopolysaccharides(LPS) for 16 hours. Culture medium were collected and measured for IL-6, TNF-a, COX-2 and eNOS protein expression and NO level by using Enzyme-linked immunosorbent assay (ELISA) and colorimetric assay respectively…